1966
DOI: 10.1099/00221287-44-2-293
|View full text |Cite
|
Sign up to set email alerts
|

Function and Location of a "Germination Enzyme" in Spores of Bacillus Cereus

Abstract: SUMMARYAn enzyme extracted from Bacillus cereus spores caused to germinate spores of this organism which had been sensitized by reagents which rupture disulphide bonds. Inactivation of the enzyme by thiol-blocking agents and by oxidation, and reactivation by reduction suggested that the enzyme's ability to germinate spores depended on thiol groups. No evidence was obtained to support the hypothesis that the enzyme was present in dormant spores in the oxidized inactive form and became reduced and active during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1

Year Published

1970
1970
1990
1990

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 16 publications
0
25
1
Order By: Relevance
“…Since then, the spore-lytic enzymes of Bacillus cereus have been isolated and extensively studied by Strange & Dark (1957), Gould et al (1966), Warth (1972) and Brown et al (1975Brown et al ( , 1977Brown et al ( , 1978. In most cases, this lytic system was found to hydrolyse the peptidoglycan of the spore cortex, resulting in germination-like changes in the spore.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the spore-lytic enzymes of Bacillus cereus have been isolated and extensively studied by Strange & Dark (1957), Gould et al (1966), Warth (1972) and Brown et al (1975Brown et al ( , 1977Brown et al ( , 1978. In most cases, this lytic system was found to hydrolyse the peptidoglycan of the spore cortex, resulting in germination-like changes in the spore.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme was assayed by its ability to cause a decrease in the extinction of suspensions of spores which had been sensitized by incubation in thioglycollic (mercaptoacetic) acid (25 %, v/v) plus urea (6 M) at 70" for 30 min. (Gould et al 1966). The enzyme reaction was carried out in sodium phosphate buffer (100 mM, pH 8.0) at 37"; the initial extinction read at 580 nm.…”
Section: Inhibition Of Spore Germination 303mentioning
confidence: 99%
“…to 20 mg. dry wt/ml.) which had been disrupted by shaking with glass beads as described by Gould, Hitchins & King (1966). The enzyme was assayed by its ability to cause a decrease in the extinction of suspensions of spores which had been sensitized by incubation in thioglycollic (mercaptoacetic) acid (25 %, v/v) plus urea (6 M) at 70" for 30 min.…”
Section: Inhibition Of Spore Germination 303mentioning
confidence: 99%
“…Although the mechanism initiating these changes is not known, Strange & Dark (1957) and Gould, Hitchins & King (1966) suggested that they result more or less directly from depolymerization of peptidoglycan in the spore cortex, catalysed by a lytic enzyme which can be extracted from spores of some species and which can be shown to cause germination-like changes in chemically sensitized spores (Gould & King, 1969). If this is so then the excretion of peptidoglycan fragments would be expected to be one of the earliest determinable events during germination.…”
mentioning
confidence: 99%